2013
DOI: 10.1155/2013/704589
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Recovery Outcome after Digital Nerve Repair in Relation to Different Reconstructive Techniques: Meta-Analysis and Systematic Review

Abstract: Good clinical outcome after digital nerve repair is highly relevant for proper hand function and has a significant socioeconomic impact. However, level of evidence for competing surgical techniques is low. The aim is to summarize and compare the outcomes of digital nerve repair with different methods (end-to-end and end-to-side coaptations, nerve grafts, artificial conduit-, vein-, muscle, and muscle-in-vein reconstructions, and replantations) to provide an aid for choosing an individual technique of nerve rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 92 publications
(103 reference statements)
1
66
1
2
Order By: Relevance
“…13 Two-point discrimination on the operated side was significantly higher with 9 mm, suggesting that sensibility after epineural coaptation of transected digital nerves most probably does not recover to a restitutio ad integrum, which is in line with previous findings. 8,10,26 For the grating orientation test, too, we found an average value of 2.5 mm on the operated side-significantly differing from the average grating orientation test result of 1.0 mm on the healthy side. Comparable (normative) data for grating orientation test performed on healthy fingertips are rare throughout the literature: Tremblay et al analyzed the grating orientation test threshold in a healthy adult series (n = 21) aged between 60 and 70 years resulting in a mean grating orientation test score of 2.7 ± 0.6 mm.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…13 Two-point discrimination on the operated side was significantly higher with 9 mm, suggesting that sensibility after epineural coaptation of transected digital nerves most probably does not recover to a restitutio ad integrum, which is in line with previous findings. 8,10,26 For the grating orientation test, too, we found an average value of 2.5 mm on the operated side-significantly differing from the average grating orientation test result of 1.0 mm on the healthy side. Comparable (normative) data for grating orientation test performed on healthy fingertips are rare throughout the literature: Tremblay et al analyzed the grating orientation test threshold in a healthy adult series (n = 21) aged between 60 and 70 years resulting in a mean grating orientation test score of 2.7 ± 0.6 mm.…”
Section: Discussioncontrasting
confidence: 84%
“…Assessment of sensory recovery after digital nerve transection thereby plays a major role and has thus been addressed by numerous studies in recent decades. [1][2][3][4][5][6][7][8][9][10] To date, a plethora of test instruments is available to expediently evaluate sensory recovery after transection of nerves. 11 Regrettably, all of these are associated with different drawbacks.…”
Section: Hand/peripheral Nervementioning
confidence: 99%
“…Median and ulnar nerve injuries at the wrist, forearm, and proximal to the elbow were included and there were only two patients with injuries distal to the wrist. A recent systematic review and meta-analysis of the results for digital nerve repair or reconstruction using various techniques reported similar results (Paprottka et al, 2013). No particular technique had significantly different outcomes, except that end-to-side repairs were not as reliably successful as end-to-end repairs or reconstructions.…”
Section: Discussionmentioning
confidence: 96%
“…Future aims of this project could include testing the use of this device in combination with autografts, allografts, or other established conduits. Paprottka et al meta-analysis showed that regardless of the technique used in repairing sensory digital nerve, recovery was 42% and excellent recovery 25% [12]. If including our device into the repertoire of nerve synthesis we can improve this statistics, not only our study will be fulfilled, this will also translate into more productive and satisfied patients.…”
Section: Discussionmentioning
confidence: 85%